Pilot study on the effects of assertion video viewing and physical activity on depressive symptoms in workers witnessing workplace bullying - Atsuo Hattori; Yasumasa Otsuka (Discover Psychology)
Abstract Background Studies have reported that depressive symptoms in individuals who witness workplace bullying are worsening. Consequently, companies in Japan were legally obligated to implement the necessary employment management regulations to prevent workplace bullying in 2019. Notably, assertion and physical activities can reduce depressive symptoms. This study examined the effects of assertion video viewing and physical activity interventions on depressive symptoms in workers who witnessed workplace bullying. Methods Forty-five Japanese adults participated in this study. After viewing the workplace bullying video, the participants were randomly divided into three groups: assertion video viewing, physical activity, and control. Depressive symptoms were assessed by the Multiple Mood Scale before the intervention (T1), after viewing the video (T2), and immediately after the intervention (T3). Two-factor analysis of variance was conducted with group and time as independent variables and depressive symptoms as the dependent variable. Results Analysis of variance revealed that the interaction effect was significant. Simple main effect analysis revealed that depressive symptom scores at T3 were significantly lower than those at T2 in the assertion group and that depressive symptom scores at T3 were significantly lower than those at T1 and T2 in the physical activity group. Conclusions Video viewing and physical activity may ameliorate depressive symptoms in workers who have witnessed workplace bullying.